2019
DOI: 10.2337/dc19-1580
|View full text |Cite
|
Sign up to set email alerts
|

Superior Long-term Survival for Simultaneous Pancreas-Kidney Transplantation as Renal Replacement Therapy: 30-Year Follow-up of a Nationwide Cohort

Abstract: OBJECTIVE In patients with type 1 diabetes and end-stage renal disease, it is controversial whether a simultaneous pancreas-kidney (SPK) transplantation improves survival compared with kidney transplantation alone. We compared long-term survival in SPK and living- or deceased-donor kidney transplant recipients. RESEARCH DESIGN AND METHODS We included all 2,796 patients with type 1 diabetes in the Netherlands who started renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…We have not taken into consideration the benefits of living donor kidney transplantation or PAK transplantation due to insufficient sample size. The survival benefits of these transplant options in comparison to SPK have been analysed elsewhere [11,19,36,37]. In our modelling, we have not accounted for the potential benefits of re‐transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not taken into consideration the benefits of living donor kidney transplantation or PAK transplantation due to insufficient sample size. The survival benefits of these transplant options in comparison to SPK have been analysed elsewhere [11,19,36,37]. In our modelling, we have not accounted for the potential benefits of re‐transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Esmeijer et al . [19] explored the relative survival benefits of transplantation compared with dialysis in patients with type 1 diabetes mellitus in a Dutch cohort. They found a considerable survival advantage for transplanted recipients (deceased or living donor kidney or SPK) compared to waitlisted patients on dialysis, with 5‐year survival 76% vs. 32%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, simultaneous kidney and pancreas transplantation is associated with a survival benefit compared to kidney transplantation alone, with the 10-year survival of 67% in simultaneous kidney and pancreas transplant recipients compared to 56% and 36% in kidney transplant recipients from a living or deceased donor, respectively [1,15]. All-cause mortality in simultaneous kidney and pancreas transplant recipients was 20-30% lower compared to a deceased donor kidney transplant recipients during 10-and 20-year followup, and 20% lower compared a living donor kidney transplant recipients during 20-year follow-up [16].…”
Section: Worsening Of Retinopathymentioning
confidence: 97%
“…Esmeijer et al compared long-term survival in SPK and LDKT or deceased-donor kidney transplant (DDKT) recipients with T1DM and renal failure on renal replacement therapy. 4 They found that median (95% confidence interval [CI]) patient survival time was 7.3 (6.2-8.3), 10.5 (7.2-13.7), and 16.5 (15.1-17.9) years after deceased-donor, livingdonor, and SPK transplants, respectively. SPK recipients with a functioning pancreas graft at 1 year (91%) had the highest survival (median 17.4 years).…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%
“…The authors contend that these results should encourage the adoption of SPK transplantation with T1DM and renal failure on renal replacement therapy. 4 The use of SPK in type 2 diabetic mellitus (T2DM) patients remains limited compared with T1DM patients. Alhamad et al studied the national transplant registry of 35 849 T2DM patients with end-stage renal disease (ESRD) with or without renal replacement therapy who received transplants between 2000 and 2016.…”
Section: Kidney Transplantation (Kt)mentioning
confidence: 99%